Characterizing immune-mediated adverse events with durvalumab in patients with unresectable stage III NSCLC: A post-hoc analysis of the PACIFIC trial. (April 2022) - Naidoo, Jarushka; Vansteenkiste, Johan F.; Faivre-Finn, Corinne; Özgüroğlu, Mustafa; Murakami, Shuji; Hui, Rina; Quantin, Xavier; Broadhurst, Helen; Newton, Michael; Thiyagarajah, Piruntha; Antonia, Scott J.
Highlights: Grade 3/4 and fatal imAEs were uncommon with durvalumab after CRT. Pneumonitis and thyroid disorders were the most common imAEs with this regimen. ImAEs typically occurred within 3 months of durvalumab initiation. In general, imAEs were well managed with appropriate clinical intervention. Time elapsed between RT and randomization did not impact imAE incidence or severity. Abstract: Introduction: Immune-mediated adverse events (imAEs), including all-cause immune-mediated pneumonitis, were reported in approximately 25% of patients in the placebo-controlled, phase III PACIFIC trial of durvalumab monotherapy (for up to 12 months) in patients with unresectable, stage III NSCLC and no disease progression after concurrent chemoradiotherapy; only 3.4% of patients experienced grade 3/4 imAEs. With broad application of the PACIFIC regimen (consolidation durvalumab after chemoradiotherapy), now standard-of-care in this setting, there is a need to better characterize the occurrence of imAEs with this regimen. Methods: We performed descriptive, post-hoc, exploratory analyses to characterize the occurrence of imAEs (pneumonitis and non-pneumonitis) in PACIFIC in terms of: incidence, severity, and timing; clinical management and outcomes; and associations between the occurrence of imAEs and (1) all-cause AEs and (2) baseline patient, disease, and treatment characteristics. Results: Any-grade immune-mediated pneumonitis (9.4%) and non-pneumonitis imAEs (10.7%) occurred infrequently and were more common with durvalumab versus placebo. Grade 3/4 immune-mediated pneumonitis (1.9%) and non-pneumonitis imAEs (1.7%) were uncommon with durvalumab, as were fatal imAEs (0.8%; all pneumonitis). The most common non-pneumonitis imAEs with durvalumab were thyroid disorders, dermatitis/rash, and diarrhea/colitis. Dermatitis/rash had the shortest time to onset (from durvalumab initiation), followed by pneumonitis; dermatitis/rash had the longest time to resolution, followed by thyroid disorders. Most patients with immune-mediated pneumonitis (78.4%) and non-pneumonitis imAEs (56.3%) had these events occur ≤ 3 months after initiating durvalumab. ImAEs were well managed with administration of systemic corticosteroids, administration of endocrine replacement therapy, and interruption/discontinuation of durvalumab. Time elapsed from completion of prior radiotherapy to trial randomization (<14 vs. ≥ 14 days) did not impact either incidence or severity of imAEs. Durvalumab had a manageable safety profile broadly irrespective of whether patients experienced imAEs. Conclusion: The risk of imAEs should not deter use of the PACIFIC regimen in eligible patients, as these events are generally well managed through appropriate clinical intervention.